2017
DOI: 10.1007/s00256-017-2768-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiple skeletal muscle metastases revealing a cardiac intimal sarcoma

Abstract: We report the case of a 59-year-old female with progressive bilateral painful swelling of the thighs. MRI revealed multiple intramuscular necrotic masses with similar morphologic patterns. Whole-body CT and 18-FDG PET-CT scans demonstrated additional hypermetabolic muscular masses and a lobulated lesion within the left atrial cavity. As biopsy of a muscular mass was compatible with a poorly differentiated sarcoma with MDM2 oncogene amplification, two diagnoses were discussed: a dedifferentiated liposarcoma wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…In addition, we detected a small segment 12q gain (4 copies) containing CDK4 gene and a nearby 9 copies-amplification containing MDM2 gene. Our results further support previous findings in an oral inflammatory myofibroblastic tumor23 and in two primary cardiac tumors24,25 and provide a rationale for applying precision medicine approaches to these types of tumors with TP53 therapy (PRIMA-1 or MDM2 inhibitors) and CDK4 inhibitors such as palbociclib. The neoplastic nature of inflammatory myofibroblastic tumors and the possible relation with inflammatory events are still debated: some exceptional spontaneous or steroid-induced regression has been described,26 but surgical resection remains the treatment of choice.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we detected a small segment 12q gain (4 copies) containing CDK4 gene and a nearby 9 copies-amplification containing MDM2 gene. Our results further support previous findings in an oral inflammatory myofibroblastic tumor23 and in two primary cardiac tumors24,25 and provide a rationale for applying precision medicine approaches to these types of tumors with TP53 therapy (PRIMA-1 or MDM2 inhibitors) and CDK4 inhibitors such as palbociclib. The neoplastic nature of inflammatory myofibroblastic tumors and the possible relation with inflammatory events are still debated: some exceptional spontaneous or steroid-induced regression has been described,26 but surgical resection remains the treatment of choice.…”
Section: Discussionsupporting
confidence: 90%
“…Scattered case reports in literature describe how integrated PET/CT with FDG imaging can incidentally show cardiac neoplasia, particularly metastatic involvement, 11 17 or may be used in case of suspected aggressive cardiac malignancy to strengthen the diagnosis and detect possible occult distant disease. 18 26 …”
Section: F-fluorodeoxyglucose Positron Emission Tomogramentioning
confidence: 99%
“…Findings suggestive of a malignant cardiac tumor at MRI include: right atrial location; involvement of more than one cardiac chamber, size > 5 cm, hemorrhagic pericardial effusion, broad base of attachment, extension into the mediastinum or great vessels and a 'moderate,' 'strong,' or heterogeneous delayed enhancement pattern. 10 18 F-fluorodeoxyglucose positron emission tomography/computed tomography Scattered case reports in literature describe how integrated PET/CT with FDG imaging can incidentally show cardiac neoplasia, particularly metastatic involvement, [11][12][13][14][15][16][17] or may be used in case of suspected aggressive cardiac malignancy to strengthen the diagnosis and detect possible occult distant disease. [18][19][20][21][22][23][24][25][26] However, unlike many other solid tumors, FDG PET does not have an established role in the routine evaluation of cardiac tumors, which is probably due both to their low frequency and to the physiologically high uptake of FDG in the myocardium, although with interindividual and intraindividual variability.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…Liver transplantation offers the advantage of radical treatment for HCC, as it can remove the tumor and restore normal liver function. The occurrence SMM, a malignant tumor that often occurs in patients with advanced cancer and appears to be a sign of systemic hematogenous metastases, is rare after liver transplant[ 3 , 4 ]. Almusarhed et al [ 5 ] reported a case of solitary biceps muscle metastasis from breast cancer, 6 mo after postoperative chemotherapy combined with endocrine therapy.…”
Section: Discussionmentioning
confidence: 99%